AIR TRAFFIC CONTROLLERS ASSISTANCE IN PROVISION OF TRAFFIC SEPARATION - Bogunenko, Mykola; Raksha, Karyna (Proceedings of National Aviation University (archive), 2015)
This article is devoted to general overview of the methods to reduce ATC workload by implementing supplementary tools for providing separation. It is also provided with recommendations on optimization of decision making process based on relevant researches.